Review on recent progress and reactor set-ups for hydrogen production from formic acid decomposition. (December 2022) - Hafeez, S.; Harkou, E.; Spanou, A.; Al-Salem, S.M.; Villa, A.; Dimitratos, N.; Manos, G.; Constantinou, A.
Abstract: Hydrogen is a clean and efficient energy carrier, and a hydrogen-based economy is an alternative solution for sustainability. The present work reviews the recent progress for hydrogen's production from various technologies including the generation from fossil fuels, from biomass through biological and thermochemical processes and from water splitting. Although hydrogen is a zero-emission energy when it is used, its cleanness depends on the production pathway that preceded. Hydrogen's storage and transportation has been costly and an unsafe procedure; formic acid (FA; CH2 O2), on the other hand, can be generated, transported, and decomposed easily to hydrogen. Formic acid is generated from the hydrogenation of atmospheric carbon dioxide (CO2 ) and can easily be provided with energy portable devices, vehicles, and other applications. In addition, the most widely known homogeneous and heterogeneous catalysts and reactors for the formic acid reaction are presented. Different types of reactors like, fixed-bed reactors (FBRs), batch reactors, continuously stirred tank reactors (CSTRs) and microreactors were assessed for their performance and reaction's efficiency during formic acid's decomposition. Highlights: A recent review on reactor set-ups for hydrogen (H2 ) production via formic acid decomposition. Homogeneous and heterogeneous catalysts are thoroughly presented. (FBRs), batch reactors, continuously stirred tank reactors (CSTRs) and microreactors are assessed for their performance. Reaction and catalytic parameters during the reaction are discussed.